Trends and spatial distribution of low-level viremia among Ugandan children and adolescents, 2014–2023 - Janet Kobusinge Lubega; Patrick Twesigye; Richard Migisha; Lilian Bulage; Benon Kwesiga; Proscovia Nambuya; Isaac Sewanyana; Eleanor Namusoke Magongo; Alex Riolexus Ario (PLoS ONE, 2026)
Background Low-level viremia (LLV) is as an early warning signal for treatment failure and onward transmission risk. Uganda has achieved major progress in expanding viral load (VL) testing coverage, yet the burden and trends of LLV among children and adolescents living with HIV (CALHIV) remain insufficiently described. This study assessed national LLV prevalence, temporal trends, and regional distribution from 2014–2023 to guide pediatric HIV program planning. Methods We analyzed routine VL data from Uganda’s Laboratory Information Management System (LIMS) housed at the Central Public Health Laboratories for CALHIV aged 0–19 years with VL results between 2014 and 2023. Viral suppression was defined as <200 copies/mL for plasma and <400 copies/mL for dried blood spot (DBS) samples. LLV was categorized as 201–999 copies/mL for plasma and 401–999 copies/mL for DBS. We analyzed LLV proportions over time and disaggregated them by demographic (age, sex), clinical (ART regimen, duration on ART, adherence, WHO stage), and facility-level (ownership, level of care) characteristics. The Mann-Kendall trend test was used to assess the significance of observed trends. Results A total of 974,873 VL tests were analyzed, of which LLV accounted for 14% (138,126). Nationally, LLV increased from 10.5% in 2014 to 16.2% in 2023 (p < 0.001). LLV rose in both males (10.7% to16.9%, p < 0.001) and females (10.3% to15.6%, p = 0.025), with the steepest increase among infants (12.7%to 22.5%, p < 0.001). Increases were observed among CALHIV on first-line regimens (10.2% to15.7%, p < 0.01), those on ART ≥ 5 years (12.5% to17.8%, p < 0.01), and those with good adherence (10.2% to14.9%, p < 0.001). In 2023, five of fifteen regions recorded LLV prevalence above 20%. Conclusion The rising LLV burden among CALHIV in Uganda signals emerging virologic challenges that may compromise long-term treatment outcomes. Strengthening VL monitoring, early detection of LLV, and tailored adherence interventions are critical to sustaining viral suppression and preventing progression to high-level viremia.